Author Correction: Nutrients cause grassland biomass to outpace herbivory - Borer, E. T.; Harpole, W. S.; Adler, P. B.; Arnillas, C. A.; Bugalho, M. N.; Cadotte, M. W.; Caldeira, M. C.; Campana, S.; Dickman, C. R.; Dickson, T. L.; Donohue, I.; Eskelinen, A.; et al. (Springer Nature, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-021-20985-z.
Author Correction: Nutrients cause grassland biomass to outpace herbivory (Nature Communications, (2020), 11, 1, (6036), 10.1038/s41467-020-19870-y)